Assessment of Biological and Anti-Cancer Activity, Design of Some Novel Heterocyclic Compounds, And Synthesis Based on Indole-Dione - Rana S. Al-Shemary (Central Asian Journal of Medical and Natural Science, 2023)
This search included synthesized new hertocyclic derivatives from Isatin (T) via reaction with 4-aminobenzoic acid to give (T2) ,and with SOCl2 to give compound (T1) , esterfication to give (T3), reacted with hydrazine to give (T4) compound ,and with anhydrides to give(T5,T6) .The schiff base (T10) prepared from benzylaldehyde and (T9) perpared fram (T2) and thiocarbohydrazide .(T8) compound synthesized fram (T2) and semicarbzide by aring closer reaction in NaOH. This (T1-T10) compounds were measured biological and anticancer activity and give high good activity with (IC50=42.18,45.02 for compounds 12 and 3).